2021
DOI: 10.1101/2021.12.09.21267203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced Odds of SARS-CoV-2 Reinfection after Vaccination among New York City Adults, June–August 2021

Abstract: BackgroundBelief in immunity from prior infection and concern that vaccines might not protect against new variants are contributors to vaccine hesitancy. We assessed effectiveness of full and partial COVID-19 vaccination against reinfection when Delta was the predominant variant in New York City.MethodsWe conducted a case-control study in which case-patients with reinfection during June 15– August 31, 2021 and control subjects with no reinfection were matched (1:3) on age, sex, timing of initial positive test … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…11 Emerging evidence suggests that vaccination with ChAdOx1 nCoV-19 (AstraZeneca), Ad26.COV2.S (Janssen), BNT162b2 (tozinameran; Pfizer-BioNtech), or mRNA-1273 (elasomeran; Moderna) confers additional protection against symptomatic reinfection among individuals with previous SARS-CoV-2 infection. [12][13][14][15][16][17][18] However, only one study has assessed protection against severe outcomes in previously infected individuals, with just 75 hospital admissions and two deaths. 18 Moreover, data for inactivated vaccines, which account for almost half of all doses given globally, are still needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Emerging evidence suggests that vaccination with ChAdOx1 nCoV-19 (AstraZeneca), Ad26.COV2.S (Janssen), BNT162b2 (tozinameran; Pfizer-BioNtech), or mRNA-1273 (elasomeran; Moderna) confers additional protection against symptomatic reinfection among individuals with previous SARS-CoV-2 infection. [12][13][14][15][16][17][18] However, only one study has assessed protection against severe outcomes in previously infected individuals, with just 75 hospital admissions and two deaths. 18 Moreover, data for inactivated vaccines, which account for almost half of all doses given globally, are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] However, only one study has assessed protection against severe outcomes in previously infected individuals, with just 75 hospital admissions and two deaths. 18 Moreover, data for inactivated vaccines, which account for almost half of all doses given globally, are still needed. 19 Brazil has recorded more than 22 million SARS-CoV-2 infections and 600 000 deaths as of Nov 15, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…20 To our knowledge, only one prior study reported vaccine effectiveness among previously infected individuals against COVID-19 related hospitalization or death; with just 75 outcomes and three vaccines evaluated, power in that study was limited for assessing vaccine and dose-specific effectiveness, but estimates ranged from 58% (BNT162b2) to 68% (mRNA-1273), with no significant protection from Ad26.COV2.S. 19 We found that protection against these severe outcomes, from 14 days after the second dose, was greater than 80% for the three two-dose vaccines (CoronaVac, ChAdOx1, and BNT162b2). These results are consistent with recent data showing that previously infected individuals have even greater increases in T-cell and B-cell responses following vaccination compared with those without prior infection.…”
Section: In This Nationwide Population-based Study Among Individuals With Confirmed Prior Sars-mentioning
confidence: 99%
“…12 Emerging evidence suggests that vaccination with ChAdOx1, Ad26.COV2.S, BNT162b2, or mRNA-1273 does confer additional protection against symptomatic reinfection among individuals with prior SARS-CoV-2 infection. [13][14][15][16][17][18][19] However, only one study has assessed protection against severe outcomes, with just 75 hospitalizations and 2 deaths. 19 Moreover, data for inactivated vaccines, which account for almost half of all doses given globally, are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation